Chylous Fistula following Axillary Lymphadenectomy: Benefit of Octreotide Treatment - Elena González-Sánchez-Migallón; José Aguilar-Jiménez; José Andrés García-Marín; José Luis Aguayo-Albasini (Case Reports in Surgery)
Chyle leak following axillary lymph node clearance is a rare yet important complication. The treatment of postoperative chyle fistula still remains unclear. Conservative management is the first line of treatment. It includes axillary drains on continuous suction, pressure dressings, bed rest, and nutritional modifications. The use of somatostatin analogue is well documented as a treatment for chylous fistulas after neck surgery. We present a case of chylous fistula after axillary surgery resolved with the use of octreotide.